2022
DOI: 10.21037/atm-22-1578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acellular nerve scaffold containing human umbilical cord-derived mesenchymal stem cells on nerve repair and regeneration in rats with sciatic nerve defect

Abstract: Background:The aim of the present study was to investigate the effect of acellular nerve scaffold (ANS) containing human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) on nerve repair and regeneration in rats with sciatic nerve defect.Methods: Sciatic nerve trunks were removed from 6 female Sprague-Dawley (SD) rats, and ANS was prepared by lyophilization + enzymatic method and divided into A, B, C, D and E groups according to different treatment times. hUC-MSCs were isolated from the collected umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, no significant differences were found among the DPNAs studied. These results agree with most articles in which better muscle trophism was obtained in animals treated with nerve autografts than bioengineered nerve substitutes ( Debski et al, 2021 ; Yu et al, 2021 ) and DPNAs ( Zheng et al, 2014 ; Chato-Astrain et al, 2020b ; Qian et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, no significant differences were found among the DPNAs studied. These results agree with most articles in which better muscle trophism was obtained in animals treated with nerve autografts than bioengineered nerve substitutes ( Debski et al, 2021 ; Yu et al, 2021 ) and DPNAs ( Zheng et al, 2014 ; Chato-Astrain et al, 2020b ; Qian et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…The hUCMSCs could reduce or block MHC class II expressions on vascular endothelial cell surface in cardiac allografts and decrease proinflammatory cytokines IL2 and IFN-γ, enhance anti-inflammatory cytokines, such as IL10 and TGF-β1 expression in vivo. The soluble factors secreted by hUC-MSC have immunoregulatory effects as well [22 ]. For more than a decade there are several attempts exploring the use of umbilical cord as a graft for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…A novel method using lyophilization and enzymes to prepare Acellular Nerve Scaffold (ANS) was effective in removal of cells, myelin and and maintain the integrity and mechanical properties of nerve fiber than the traditional methods. The combination of hUC-MSCs with ANS promotes repair and regeneration of the sciatic nerve SD animal model [ 20,22 ]. In another similar studies Tonsils derived Mesenchymal stem cells (T-MSCs) were differentiated to Schwann cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have indicated that certain miRNAs, such as miR-23a, can alleviate muscle atrophy by reducing the mRNA levels of MuRF1 and MuRF2. 33 Human umbilical cord MSCs alleviate muscle atrophy caused by conditions such as diabetes, 34 age-associated sarcopenia, 35 nerve defect, 36 Huntington’s disease, 37 and ischemic. 38 Currently, there are few studies on the use of human umbilical cord MSCs and their derived exosomes for the treatment of muscle atrophy following nerve injury.…”
Section: Introductionmentioning
confidence: 99%